Aktifitas Fisik Berhubungan dengan Kualitas Hidup Lansia Penderita Hipertensi - Putri, Mawar Eka; Kurniati, Safra Ria; Agustiar, Evan (Fakultas Ilmu Kesehatan, 2024)
As we age, an individual experiences changes including changes in physiological, psychological and socio-economic status. Elderly people continually experience various changes marked by decreased physical endurance, making them vulnerable to disease attacks, one of which is hypertension, which can cause reduced physical activity. Lack of physical activity increases the risk of developing hypertension. Physical activity can improve the quality of life of elderly people, including elderly people with hypertension. The aim of this study was to determine the relationship between physical activity and the quality of life of elderly people with hypertension. The research method is non-experimental with a cross-sectional approach. Data were analyzed using Chi Square. Instruments used WHO GPAQ Physical Activity and WHOQL-BREF quality of life. The research subjects were elderly people with hypertension. The results of the study showed a p-value of 0.003, where there was a relationship between physical activity and the quality of life of elderly people with hypertension with p < 0.05. Conclusion: There is a relationship between physical activity and quality of life in elderly people with hypertension